2020
DOI: 10.1051/e3sconf/202018705002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a seedling tray seeder for lettuce (Lactuca sativaL.) production

Abstract: Conventional method of sowing lettuce is laborious and time consuming. Thus, this study was conducted to develop a seedling tray seeder for lettuce. Specifically, it aimed to design a seeder, fabricate the design, evaluate the field performance parameters, and analyze the cost of operation of using the machine. The machine was fabricated based on the design plan which was comprised of the dibbler unit, seed metering unit, soil covering unit, power transmission system, automation unit and frame assembly. Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Interestingly, numerous studies have pointed out that the right pneumatic state is crucial for obtaining high quality seeding performance. In the field trials of a low-cost seedling tray seeder for lettuce, Tiw-An et al (2020) found that the seeding effectiveness of the device was dramatically influenced by the vacuum level. Increasing the vacuum pressure was found to be an effective way to improve the seed suction capacity of tray seeder by C. Liu et al (2010), and similar experimental results were also found in Xia et al (2008) and Hassan and Liao (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, numerous studies have pointed out that the right pneumatic state is crucial for obtaining high quality seeding performance. In the field trials of a low-cost seedling tray seeder for lettuce, Tiw-An et al (2020) found that the seeding effectiveness of the device was dramatically influenced by the vacuum level. Increasing the vacuum pressure was found to be an effective way to improve the seed suction capacity of tray seeder by C. Liu et al (2010), and similar experimental results were also found in Xia et al (2008) and Hassan and Liao (2014).…”
Section: Introductionmentioning
confidence: 99%